Mengembangkan Model Ideal Pendidikan Islami - Hujair AH. Sanaky (EL-TARBAWI, 2014)
The critical points towards traditional Islamic education is its inability to solve contemporary problems in modern life. Therefore, to deal with these problems, Islamic education institutions should rethink and redesign Islamic education model which is not only focused on normative values (traditional religious teaching), but also focused on empirical issues. It is urgent to develop ideal model of Islamic education, since the challenges resulted from change in human life that strongly driven by economics, sophisticated technology and science development are growing rapidly. This paper proposes Islamic education model design, which is based on some thoughts of contemporary Muslim scholars. The model is expected to give alternative idea about how to design and develop a future Islamic education system.